Patient-reported Outcomes: the ICHOM Standard Set for Inflammatory Bowel Disease in Real-life Practice Helps Quantify Deficits in Current Care. (22nd July 2022) - Wong, Darren; Matini, Lawrence; Kormilitzin, Andrey; Kantschuster, Ramona; Simadibrata, Daniel Martin; Lyden, Sara; Wilson, Jean; Brain, Oliver A; Palmer, Rebecca; Ambrose, Tim; Satsangi, Jack; South, Matthew; et al.
Abstract: Background: Patient-reported outcome measures [PROMs] are key to documenting outcomes that matter most to patients and are increasingly important to commissioners of health care seeking value. We report the first series of the ICHOM Standard Set for Inflammatory Bowel Disease [IBD]. Methods: Patients treated for ulcerative colitis [UC] or Crohn's disease [CD] in our centre were offered enrolment into the web-based TrueColours-IBD programme. Through this programme, e-mail prompts linking to validated questionnaires were sent for symptoms, quality of life, and ICHOM IBD outcomes. Results: The first 1299 consecutive patients enrolled [779 UC, 520 CD] were studied with median 270 days of follow-up (interquartile range [IQR] 116, 504). 671 [52%] were female, mean age 42 years (standard deviation [sd] 16), mean body mass index [BMI] 26 [sd 5.3]. At registration, 483 [37%] were using advanced therapies. Median adherence to fortnightly quality of life reporting and quarterly outcomes was 100% [IQR 48, 100%] and 100% [IQR 75, 100%], respectively. In the previous 12 months, prednisolone use was reported by 229 [29%] patients with UC vs 81 [16%] with CD, p  <0.001; 202 [16%] for <3 months; and 108 [8%] for >3 months. An IBD-related intervention was reported by 174 [13%] patients, and 80 [6%] reported an unplanned hospital admission. There were high rates of fatigue [50%] and mood disturbance [23%]. Conclusions: Outcomes reported by patients illustrate the scale of the therapeutic deficit in current care. Proof of principle is demonstrated that PROM data can be collected continuously with little burden on health care professionals. This may become a metric for quality improvement programmes or to compare outcomes.